Practicality Assessment of Student Worksheets for SMP Physics Learning on the Traditional Culture-Based Equipment - Fakhruddin Z Fakhruddin Z; Lilia Halim; T. Subahan Mohd Meerah (Journal of Educational Sciences, 2017)
The purpose of this study is to examine the practicality of Student Worksheets (LKS) physics learning at junior high school (SMP) for validated traditional culture-based tools. The topic of the LKS is simple machine. The method used in the study is a research and development. The research was conducted at the Junior High School in Pekanbaru which the data source was from three science teachers and thirty students of class VIII. The LKS practicalities data was obtained through questionnaires practicalities of the device which was given to teachers and students. The analysis of the data used descriptive analysis that is to categorize the average score on learning process. Based on the analysis of the data, the practicality of the LKS has an average with the excellent category for all aspects. This shows the LKS of physics learning at junior high school based on the traditional culture equipment on the topic of simple machine practical can be used as a medium of learning physics at junior high school.